Molecular microbial diversity in soils from eastern Amazonia: evidence for unusual microorganisms and microbial population shifts associated with deforestation. - Borneman, J (1997)
Although the Amazon Basin is well known for its diversity of flora and fauna, this report represents the first description of the microbial diversity in Amazonian soils involving a culture-independent approach. Among the 100 sequences of genes coding for small-subunit rRNA obtained by PCR amplification with universal small-subunit rRNA primers, 98 were bacterial and 2 were archaeal. No duplicate sequences were found, and none of the sequences had been previously described. Eighteen percent of the bacterial sequences could not be classified in any known bacterial kingdom. Two sequences may represent a unique branch between the vast majority of bacteria and the deeply branching, predominantly thermophilic bacteria. Five sequences formed a clade that may represent a novel group within the class Proteobacteria. In addition, rRNA intergenic spacer analysis was used to show significant microbial population differences between a mature forest soil and an adjacent pasture soil.